Sustainability of Boro rice cultivation in the canal irrigated command area of India. Issue 8 (26th July 2022) - Pradhan, Sucharita; Dhar, Anirban; Tiwari, Kamlesh Narayan
Abstract: A comprehensive assessment and monitoring of rice intensification in canal irrigated command areas and its consequences on groundwater dynamics have enormous importance for the water–food–energy nexus. This study analyzed the spatiotemporal transition of Boro rice cultivation, canal irrigation practices during the cultivation season, and its effect on groundwater of a pioneering multipurpose water resource project in India. The rice maps from 1989 to 2018 were generated from Landsat and Sentinel-2A images using the Iterative Self-Organizing Data Analysis Technique Algorithm (ISODATA), the normalized difference vegetation index (NDVI), and the enhanced vegetation index (EVI) to understand the historical distribution of rice cultivation. The ISODATA clustering algorithm performed well compared to the NDVI and the EVI with medium-resolution satellite images. The impact of Boro rice cultivation on groundwater resources was investigated by considering GLDAS NOAH model-based crop evapotranspiration, rainfall, and canal water supply. The area under rice cultivation increased from 33 to 66% during 1989–2018 due to its higher stress tolerance ability and productivity. However, during the cultivation period, the canal water supply was limited to the upstream and middle section of the command area, irrigating only 19% of the rice-cultivated area on average. The unavailability of the canal water supply during the cultivation season has led to 31 m of groundwater level depletion, which, if unchecked, may lead to overexploitation of groundwater in the middle and lower sections of the command area. The results of this study can be used to identify vulnerable areas that require urgent attention and accurate implementation of any agricultural or hydrological policy. HIGHLIGHTS: Spatiotemporal variations of rice cropping patterns were generated from 1989 to 2018. The Boro rice cultivation area was increased from 33 to 66% during the study period. Boro rice patterns are independent of canal regulation methods of the command area. The average canal irrigated area was only 19% of the total cultivated area. The insufficient availability of canal water has led to 31 m of groundwater level depletion. Graphical Abstract